Significant Process of Change for Elementary Teachers to Foster Functional Thinking - Asghari, Nasim (2014)
The purpose of this study was to explore a professional development program that involved 15 teachers. Functional thinking was used as a centerpiece of the program for work with teachers of Grades 1-5 during 6 months of the study. We used the concernbased adaptation model (CBAM) as a methodology to track the process of change of teachers and to understand the trajectories through which teachers may progress. Two questions guided the investigations: 1. How does implementation of the professional development program focused on functional thinking impact teachers’ concerns? 2. How did teachers’ practice change due to the implementation of the innovation program? The result of the study showed effectiveness of process of change in teachers, both in stages of concerns and level of use of the innovation. Keywords: Process of Changing. Concerns CBAM. Elementary Teachers. Functional Thinking. Arithmetics.